Preparation method of wheat-ear-shaped bismuth ferrite nanofiber wave-absorbing material
Through the sol-gel method and electrospinning process combined with compound additives, wheat spike-like bismuth ferrate nanofiber absorbent material was prepared, which solved the problems of narrow absorption band and limited absorption strength of existing bismuth ferrate nanomaterials, and achieved wide band and efficient microwave absorption performance.
Patent Information
- Application Number
- CN202510026176.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The absorption frequency band of existing bismuth ferrate nanomaterials is narrow, with limited absorption strength and poor impedance matching, resulting in insufficient microwave absorption performance.
The sol-gel method combined with electrospinning process was used to prepare the morphology and absorption properties of the bismuth ferrate nanofibers in wheat spike by adding compound additives such as ethylene glycol methyl ether, N-methylpyrrolidone, acetic acid, citric acid and isopropanol.
The prepared wheat ear-shaped bismuth ferate nanofiber absorbent material reached -36.9dB at 12.24GHz, and the effective absorption bandwidth was 6.32GHz, which significantly improved microwave absorption performance.
Smart Images

Figure CN119800555A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nanofiber wave absorbing materials and relates to a method for preparing wheat-ear-shaped bismuth ferrite nanofiber wave absorbing material. Background Art
[0002] With the rapid development of wireless technology, precision electronic equipment has emerged. The electromagnetic waves it generates can cause harm to human health. Therefore, electromagnetic pollution has become a new type of environmental pollution. Microwave absorbing materials, as important functional materials for absorbing and attenuating incident electromagnetic waves, are widely used in civil and military fields. At present, in addition to the research on the composition of microwave absorbing materials, their structural design is also a research hotspot in this field. Among the many structures, one-dimensional structures have received widespread attention due to their unique shape anisotropy and spatial confinement effects.
[0003] Electrospinning technology has been widely used to prepare one-dimensional nanofibers with high aspect ratios. In the field of electromagnetic wave absorption, fiber structures with high aspect ratios have a good promoting effect on the attenuation capacity and impedance matching of materials. These fibers can be constructed into three-dimensional network structures, which are believed to be conducive to the multiple scattering of electromagnetic waves, thereby consuming a certain amount of electromagnetic wave energy before entering the material. In addition, fiber structures with high aspect ratios are conducive to the directional movement of electrons, forming microcurrents. Due to their own resistance, electromagnetic waves are lost in the form of heat, thereby increasing the ability to absorb microwaves.
[0004] A good absorbing material must meet two basic conditions: first, consider the electromagnetic matching characteristics. When the electromagnetic wave is incident on the surface of the absorbing material, the absorbing material absorbs the electromagnetic wave energy and reduces the reflection of the electromagnetic wave; second, consider the attenuation characteristics of the absorbing material, that is, it is required to try to absorb and reduce the electromagnetic wave energy as soon as the electromagnetic wave enters the material. Bismuth ferrite (BiFeO3, BFO) is a multiferroic material with a rhombic perovskite structure, belonging to the R3c space group. Its ferroelectricity and ferromagnetism coexist at room temperature, which is conducive to electromagnetic matching. Therefore, it has important application potential in microwave absorption. However, the absorption band of bismuth ferrite nanomaterials is relatively narrow, which makes it difficult to meet the requirements of modern absorbing materials for broadband absorption; moreover, the absorption intensity is limited, and there is a certain gap compared with some high-performance absorbing materials; in addition, the impedance matching of bismuth ferrite nanomaterials is poor, resulting in relatively large reflection of electromagnetic waves on its surface, and relatively less electromagnetic wave energy absorbed into the material, thus affecting the overall microwave absorption performance.
[0005] Based on this, the present invention adds a compound additive in the process of preparing bismuth ferrite nanofibers to prepare wheat ear-shaped bismuth ferrite nanofibers, which have good application prospects in the field of wave absorption. Summary of the invention
[0006] In view of the above technical problems, the present invention aims to provide a method for preparing wheat-ear-shaped bismuth ferrite nanofiber absorbing material. The method uses a sol-gel method in combination with an electrostatic spinning process to prepare bismuth ferrite nanofibers. In the process of preparing a precursor solution by the sol-gel method, a composite additive consisting of ethylene glycol methyl ether, N-methyl pyrrolidone, acetic acid, citric acid and isopropanol is added, and then the wheat-ear-shaped bismuth ferrite nanofiber absorbing material is obtained by electrostatic spinning, drying and calcining. The preparation process of the present invention is simple and the preparation cost is low. When the prepared wheat-ear-shaped bismuth ferrite nanofiber absorbing material has a thickness of 3 mm and a frequency of 12.24 GHz, the minimum reflection loss reaches -36.9 dB, and the effective absorption bandwidth is 6.32 GHz.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a wheat-ear-shaped bismuth ferrite nanofiber absorbing material is carried out in the following steps in order:
[0009] (1) dissolving bismuth nitrate pentahydrate and ferric nitrate nonahydrate in N,N-dimethylformamide, stirring until clear and transparent, adding a compound additive, stirring evenly, and then adding a spinning aid, stirring at a stirring rate of 200-300 rpm for 7-15 hours to obtain a precursor solution;
[0010] The compound additive is ethylene glycol methyl ether, N-methyl pyrrolidone, acetic acid, citric acid and isopropanol, and the mass ratio thereof is (1-5): (1-4): (1-5) (0.1-1): (2-5);
[0011] The composite additives in the present invention synergistically affect the morphology of bismuth ferrite nanofibers, and further affect the wave absorbing performance thereof. Specifically, ethylene glycol methyl ether and isopropyl alcohol are used as solvents, and after the two are mixed, the dissolving ability of N-methyl pyrrolidone, acetic acid, citric acid and nitrates will be enhanced; the addition of N-methyl pyrrolidone is conducive to the uniform dispersion of citric acid and metal salts in the solvent, and at the same time, the polarity of the mixed solvent can be adjusted. It is a strong polar solvent, and isopropyl alcohol and ethylene glycol methyl ether are also polar solvents, but the polarity is different. N-methyl pyrrolidone can make the mixed solvent better interact with the three carboxyl groups of citric acid, thereby improving the dissolution efficiency; in addition, citric acid is used as a complexing agent, and citrate ions will react with Fe 3+ and Bi 3+ The complex is formed to control the formation process of the sol; acetic acid helps the colloid to form stably by adjusting the pH of the system, thus ensuring that the fiber is not easy to break during the sintering process;
[0012] In the present invention, the mass ratio between the compound additives is crucial, which affects the nucleation and growth process of bismuth ferrite. When the mass ratio of ethylene glycol methyl ether, N-methyl pyrrolidone, acetic acid, citric acid and isopropanol is (1-5): (1-4): (1-5) (0.1-1): (2-5), an appropriate nucleation rate and a complete wheat ear-shaped structure can be achieved; if the mass ratio of ethylene glycol methyl ether, N-methyl pyrrolidone, acetic acid, citric acid and isopropanol is greater than this mass ratio, the growth process of bismuth ferrite nanofibers will be excessively disturbed and a regular wheat ear-shaped structure cannot be formed; if the mass ratio of ethylene glycol methyl ether, N-methyl pyrrolidone, acetic acid, citric acid and isopropanol is less than this mass ratio, the proportion of additives will be insufficient, the crystallization speed and crystallization direction of the bismuth ferrite nanofibers cannot be effectively controlled, resulting in unsatisfactory crystallinity and uneven grain size, thereby affecting the overall performance of the material;
[0013] (2) electrospinning the precursor solution obtained in step (1) to obtain a bismuth ferrite nanofiber precursor;
[0014] (3) placing the bismuth ferrite nanofiber precursor obtained in step (2) in a vacuum drying oven for drying;
[0015] (4) placing the dried bismuth ferrite nanofiber precursor into a muffle furnace and calcining it to obtain a wheat ear-shaped bismuth ferrite nanofiber absorbing material;
[0016] As a limitation of the preparation method of the present invention, in step (1), the mass ratio of the bismuth nitrate pentahydrate, the ferric nitrate nonahydrate and the N,N-dimethylformamide is 1.27:1:9.34.
[0017] As a second limitation of the preparation method of the present invention, in step (1), the spinning aid is polyvinyl pyrrolidone or polyacrylonitrile.
[0018] As a third limitation of the preparation method of the present invention, in step (1), the mass ratio of bismuth nitrate pentahydrate, ethylene glycol methyl ether and spinning aid is 1: (0.97-4.86): (1.36-2.62).
[0019] As the fourth limitation of the preparation method of the present invention, in step (2), the electrospinning injection speed is 0.03-0.25 mm / min, the pinhole diameter is 20-25G, the distance between the nozzle and the roller is 15-25 cm, the receiving speed of the roller is 30-60 r / min, the spinning positive voltage is 13-20 KV, the negative voltage is 0.5-3 KV, the temperature is 20-35 ° C, and the humidity is 20-40%.
[0020] As the fifth limitation of the preparation method of the present invention, in step (3), the drying temperature is 60-100°C, the time is 8-12h, and the vacuum degree is -0.08MPa.
[0021] As a sixth limitation of the preparation method of the present invention, in step (4), the calcination process is carried out in the following order:
[0022] (a) In the first heating stage, the temperature is raised from room temperature to 260°C at a heating rate of 1-5°C / min and kept at this temperature for 1-3h;
[0023] (b) the second heating stage, heating from 260°C to 340°C at a heating rate of 1-5°C / min, and keeping the temperature for 1-3h;
[0024] (c) the third heating stage, heating from 340°C to 500°C at a heating rate of 1-5°C / min, and keeping the temperature for 1-3h;
[0025] (d) Cooling stage: cooling to room temperature with the furnace;
[0026] The calcination process in the present invention is crucial for the morphology formation of bismuth ferrite nanofibers. When the temperature is increased from room temperature to 260°C at a heating rate of 1-5°C / min, the surface adsorbed water is first decomposed, and then the nitrate loses part of the bound water, and some unstable groups on the side chain of polyvinyl pyrrolidone are broken, and its bonding effect in the bismuth ferrite fiber is gradually weakened. Due to the introduction of the compound additive, ethylene glycol methyl ether and isopropanol volatilize earlier during the sintering process, and certain pores are generated inside the fiber, providing space for the subsequent formation of the wheat ear-shaped structure. The volatilization process will affect the N, N-dimethylformamide, N-methylpyrrolidone and acetic acid. The distribution and movement of the fibers cause the concentration changes of the local particles in the fibers, which is helpful for the initial shaping of the fiber morphology. At the same time, the volatilization of acetic acid and N,N-dimethylformamide can cause the surrounding ethylene glycol methyl ether and N-methylpyrrolidone molecules to rearrange, and the concentrations of bismuth nitrate pentahydrate and ferric nitrate nonahydrate increase relatively. Bismuth ferrite will nucleate in the local supersaturated area, affecting the morphological arrangement of the fibers. N-methylpyrrolidone has a high boiling point and evaporates relatively late during the sintering process. As the temperature rises, bismuth nitrate pentahydrate and ferric nitrate nonahydrate particles will slowly evaporate with N-methylpyrrolidone to form internal crystal nuclei. In addition, during the sintering process, citrate ions react with Fe 3+ and Bi 3+The formed complex will also slowly decompose, so that the outward growth rate of metal particles during sintering is greater than the volatilization rate of organic matter (mainly polyvinyl pyrrolidone), which is conducive to the growth of metal particles on the surface of nanofibers, and keeping warm for 1-3 hours will provide enough time for the metal particles to grow on the fiber surface, so that the crystal structure is more perfect, which is conducive to the formation of regular wheat ear-shaped structure. When the sintering temperature continues to increase from 260°C to 340°C at a heating rate of 1-5°C / min, polyvinyl pyrrolidone and nitrate further decompose, and the nucleated bismuth ferrite particles grow along the diffusion direction of the solute (bismuth nitrate pentahydrate, ferric nitrate nonahydrate). Due to the volatilization of solvents (ethylene glycol methyl ether, isopropanol, N, N-dimethylformamide, N-methylpyrrolidone and acetic acid) from different positions inside and on the surface of the fiber and the different volatilization speeds, the growth speed and direction of bismuth ferrite at different positions are different, resulting in small wheat ear-shaped grains, and keeping warm for 1-3 hours will promote the growth of small wheat ear-shaped grains. When the sintering temperature continues to increase from 340°C to 500°C at a heating rate of 1-5°C / min, the decomposition reaction of polyvinyl pyrrolidone intensifies, the main chain breaks in large numbers, the bismuth ferrite grains diffuse and grow, and the metal particles on the fiber surface transform from an amorphous phase to a perovskite phase, eventually presenting a fiber morphology similar to that of wheat ears. Keeping warm for 1-3 hours provides sufficient time for the diffusion of atoms, making the crystal boundaries of the wheat ear structure more regular.
[0027] The present invention also provides the application of the wheat-ear-shaped bismuth ferrite nanofiber wave-absorbing material, and the prepared wheat-ear-shaped bismuth ferrite nanofiber is applied in the field of wave-absorbing materials.
[0028] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, which jointly determine the morphological characteristics and performance of the product.
[0029] The above technical solution has the following advantages or beneficial effects:
[0030] 1. The wheat-ear-shaped bismuth ferrite nanofibers prepared by the present invention based on the sol-gel method and the electrospinning process have a unique morphology and good wave absorbing performance;
[0031] 2. The wheat-ear-shaped bismuth ferrite nanofiber absorbing material prepared by the present invention has a minimum reflection loss of -36.9 dB when the thickness is 3 mm and the frequency is 12.24 GHz, and the effective absorption bandwidth is 6.32 GHz;
[0032] 3. The invention has simple process, low cost, excellent wave absorbing performance and good application prospect in the field of wave absorbing.
[0033] The invention is suitable for preparing wheat-ear-shaped bismuth ferrite nanofiber wave absorbing materials.
[0034] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The XRD diagram of bismuth ferrite nanofibers prepared in Example 1 and Comparative Examples 1-2 of the present invention;
[0036] Figure 2 The SEM images of bismuth ferrite nanofibers prepared in Example 1 and Comparative Examples 1-2 of the present invention are shown;
[0037] Figure 3 This is a reflection loss diagram of the wave absorbing material composited with bismuth ferrite nanofibers and paraffin prepared in Example 1 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION
[0038] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0039] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0040] Example 1
[0041] This embodiment prepares a wheat-ear-shaped bismuth ferrite nanofiber absorbing material, and the preparation process and steps are as follows:
[0042] (1) 1.029 g of bismuth nitrate pentahydrate and 0.808 g of ferric nitrate nonahydrate were dissolved in 7.55 g of N,N-dimethylformamide, and stirred until clear and transparent, and then a composite additive (the composite additive was 3 g of ethylene glycol methyl ether, 1 g of N-methylpyrrolidone, 2 g of acetic acid, 0.8 g of citric acid and 4 g of isopropanol) was added, and then 1.8 g of polyvinyl pyrrolidone was added after stirring evenly, and the mixture was stirred at a stirring rate of 200 rpm for 7 h to obtain a precursor solution;
[0043] (2) electrospinning the precursor solution obtained in step (1) to obtain a bismuth ferrite nanofiber precursor, setting the electrospinning injection speed to 0.03 mm / min, the pinhole diameter to 20G, the distance between the nozzle and the roller to 15 cm, the receiving speed of the roller to 30 r / min, the spinning positive voltage to 13 KV, the negative voltage to 0.5 KV, the temperature to 20°C, and the humidity to 20%;
[0044] (3) placing the bismuth ferrite nanofiber precursor obtained in step (2) into a vacuum drying oven and drying at 60° C. for 12 h with a vacuum degree of -0.08 MPa;
[0045] (4) The dried bismuth ferrite nanofiber precursor is placed in a muffle furnace, first heated from room temperature to 260°C at a heating rate of 1°C / min, kept warm for 1 h, then heated from 260°C to 340°C at a heating rate of 1°C / min, kept warm for 1 h, then heated from 340°C to 500°C at a heating rate of 1°C / min, kept warm for 1 h, and finally cooled to room temperature with the furnace to obtain wheat ear shaped bismuth ferrite nanofiber absorbing material.
[0046] Example 2
[0047] This embodiment prepares a wheat-ear-shaped bismuth ferrite nanofiber absorbing material, and the preparation process and steps are as follows:
[0048] (1) 1.029 g of bismuth nitrate pentahydrate and 0.808 g of ferric nitrate nonahydrate were dissolved in 7.55 g of N,N-dimethylformamide, and stirred until clear and transparent, and then a composite additive (the composite additive was 1 g of ethylene glycol methyl ether, 2 g of N-methylpyrrolidone, 1 g of acetic acid, 0.1 g of citric acid and 2 g of isopropanol) was added, stirred evenly, and then 1.4 g of polyvinyl pyrrolidone was added, and stirred at a stirring rate of 250 rpm for 12 h to obtain a precursor solution;
[0049] (2) electrospinning the precursor solution obtained in step (1) to obtain a bismuth ferrite nanofiber precursor, setting the electrospinning injection speed to 0.15 mm / min, the pinhole diameter to 22G, the distance between the nozzle and the roller to 20 cm, the receiving speed of the roller to 50 r / min, the spinning positive voltage to 15 KV, the negative voltage to 2 KV, the temperature to 30°C, and the humidity to 30%;
[0050] (3) placing the bismuth ferrite nanofiber precursor obtained in step (2) into a vacuum drying oven and drying at 80° C. for 10 h with a vacuum degree of -0.08 MPa;
[0051] (4) The dried bismuth ferrite nanofiber precursor is placed in a muffle furnace, first heated from room temperature to 260°C at a heating rate of 3°C / min, kept warm for 2 h, then heated from 260°C to 340°C at a heating rate of 3°C / min, kept warm for 2 h, then heated from 340°C to 500°C at a heating rate of 3°C / min, kept warm for 2 h, and finally cooled to room temperature with the furnace to obtain wheat ear shaped bismuth ferrite nanofiber absorbing material.
[0052] Example 3
[0053] This embodiment prepares a wheat-ear-shaped bismuth ferrite nanofiber absorbing material, and the preparation process and steps are as follows:
[0054] (1) 1.029 g of bismuth nitrate pentahydrate and 0.808 g of ferric nitrate nonahydrate were dissolved in 7.55 g of N,N-dimethylformamide, and stirred until clear and transparent, and then a composite additive (the composite additive was 5 g of ethylene glycol methyl ether, 4 g of N-methylpyrrolidone, 5 g of acetic acid, 1 g of citric acid and 5 g of isopropanol) was added, and then 2.7 g of polyvinyl pyrrolidone was added after stirring evenly, and the mixture was stirred at a stirring rate of 300 rpm for 15 h to obtain a precursor solution;
[0055] (2) electrospinning the precursor solution obtained in step (1) to obtain a bismuth ferrite nanofiber precursor, setting the electrospinning injection speed to 0.25 mm / min, the pinhole diameter to 25G, the distance between the nozzle and the roller to 25 cm, the receiving speed of the roller to 60 r / min, the spinning positive voltage to 20 KV, the negative voltage to 3 KV, the temperature to 35 ° C, and the humidity to 40%;
[0056] (3) placing the bismuth ferrite nanofiber precursor obtained in step (2) into a vacuum drying oven and drying at 100° C. for 8 h with a vacuum degree of -0.08 MPa;
[0057] (4) The dried bismuth ferrite nanofiber precursor is placed in a muffle furnace, first heated from room temperature to 260°C at a heating rate of 5°C / min, kept warm for 3 h, then heated from 260°C to 340°C at a heating rate of 5°C / min, kept warm for 3 h, then heated from 340°C to 500°C at a heating rate of 5°C / min, kept warm for 3 h, and finally cooled to room temperature with the furnace to obtain wheat ear shaped bismuth ferrite nanofiber absorbing material.
[0058] Comparative Example
[0059] In order to explore the effects of different parameters and different additives in the preparation process of the present invention on the performance of the product of the present invention, the following comparative experiments were conducted. Different bismuth ferrite nanofibers were prepared in the following comparative examples, as follows:
[0060] Comparative Example 1
[0061] This comparative example prepares bismuth ferrite nanofibers similar to those in Example 1, except that in step (1), no compound additive is added, and the other parameters are the same as those in Example 1.
[0062] Comparative Example 2
[0063] This comparative example prepares bismuth ferrite nanofibers similar to those in Example 1, except that only acetic acid is added to the compound additive in step (1), and the other parameters are the same as those in Example 1.
[0064] Comparative Example 3
[0065] The comparative example prepares bismuth ferrite nanofibers similar to those in Example 1, except that ethylene glycol methyl ether is not added to the compound additive in step (1), and the other parameters are the same as those in Example 1.
[0066] Comparative Example 4
[0067] The comparative example prepares bismuth ferrite nanofibers similar to those in Example 1, except that isopropanol is not added to the compound additive in step (1), and the other parameters are the same as those in Example 1.
[0068] Comparative Example 5
[0069] This comparative example prepares bismuth ferrite nanofibers similar to those in Example 1, except that citric acid is not added to the compound additive in step (1), and the other parameters are the same as those in Example 1.
[0070] Comparative Example 6
[0071] This comparative example prepares bismuth ferrite nanofibers similar to those in Example 1, except that N-methylpyrrolidone is not added to the compound additive in step (1), and the other parameters are the same as those in Example 1.
[0072] Comparative Example 7
[0073] The comparative example prepares bismuth ferrite nanofibers similar to those in Example 1, except that in step (3), the calcination process does not adopt a staged heating method, but is directly heated from room temperature to 500° C. at a heating rate of 5° C. / min.
[0074] Performance Testing
[0075] 0.0975 g of bismuth ferrite nanofibers prepared in Examples 1-3 and Comparative Examples 1-7 were respectively weighed and mixed with 0.0525 g of paraffin wax, and pressed into concentric rings. The electromagnetic parameters were tested with a vector network analyzer to obtain the wave absorbing performance.
[0076] like Figure 1 , is the XRD diagram of the bismuth ferrite nanofibers prepared in Example 1 and Comparative Examples 1-2 of the present invention. It can be seen from the figure that the bismuth ferrite nanofibers prepared in Example 1 and Comparative Examples 1-2 have obvious rhombohedral perovskite structure, the product has good crystallinity, and no impurity phase is generated.
[0077] Figure 2This is the SEM image of the bismuth ferrite nanofibers prepared by Example 1 of the present invention and Comparative Examples 1-2. From the figure, it can be seen that due to the unstable sol state of Comparative Examples 1 and 2, the metal salts are unevenly dispersed in the sol, presenting block-like and short rod-like morphologies, while Example 1 presents a wheat ear-like structure.
[0078] Figure 3 The reflection loss diagram of the bismuth ferrite nanofiber and paraffin composite absorbing material prepared in Example 1 and Comparative Examples 1-2 of the present invention, as can be seen from the figure, the bismuth ferrite nanofiber with a wheat ear-shaped structure prepared in Example 1 has the best absorbing performance. The unique wheat ear structure of the material and the constructed three-dimensional network structure can achieve multiple reflections and absorption of electromagnetic waves, so that when the thickness is 3 mm and the frequency is 12.24 GHz, the minimum reflection loss reaches -36.9 dB, and the effective absorption bandwidth is 6.32 GHz. Compared with Comparative Examples 1 and 2, the bandwidth of the absorbing material prepared in Example 1 is increased, and the absorbing performance is significantly improved.
[0079] The following table shows the minimum reflection loss and effective absorption bandwidth of the bismuth ferrite nanofibers prepared in Examples 2-3 and Comparative Examples 3-7 when the thickness is 3 mm. The specific values are as follows:
[0080] Minimum reflection loss (dB) Effective absorption bandwidth (GHz) Example 2 -33.86 7.68 Example 3 -29.06 6.32 Comparative Example 3 -20.7 5.44 Comparative Example 4 -15.66 6.96 Comparative Example 5 -13.8 4.48 Comparative Example 6 -14.9 4.72 Comparative Example 7 -18.94 5.12
[0081] From the above table and Figure 3 It can be seen that compared with comparative examples 1-7, the wave absorption performance of the wheat-ear-shaped nanofibers prepared in examples 1-3 is significantly improved and the bandwidth is increased.
[0082] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing wheat-ear-shaped bismuth ferrite nanofiber absorbing material, characterized in that: Follow the steps below in order: (1) dissolving bismuth nitrate pentahydrate and ferric nitrate nonahydrate in N,N-dimethylformamide, stirring until clear and transparent, adding a compound additive, stirring evenly, and then adding a spinning aid, stirring at a stirring rate of 200-300 rpm for 7-15 hours to obtain a precursor solution; The compound additive is ethylene glycol methyl ether, N-methyl pyrrolidone, acetic acid, citric acid and isopropanol, and the mass ratio thereof is (1-5): (1-4): (1-5) (0.1-1): (2-5); (2) electrospinning the precursor solution obtained in step (1) to obtain a bismuth ferrite nanofiber precursor; (3) placing the bismuth ferrite nanofiber precursor obtained in step (2) in a vacuum drying oven for drying; (4) The dried bismuth ferrite nanofiber precursor is placed in a muffle furnace for calcination to obtain a wheat-ear-shaped bismuth ferrite nanofiber absorbing material.
2. The method for preparing the wheat-ear-shaped bismuth ferrite nanofiber absorbing material according to claim 1, characterized in that: In step (1), the mass ratio of bismuth nitrate pentahydrate, ferric nitrate nonahydrate and N,N-dimethylformamide is 1.27:1:9.
34.
3. The method for preparing the wheat-ear-shaped bismuth ferrite nanofiber absorbing material according to claim 1, characterized in that: In step (1), the spinning aid is polyvinyl pyrrolidone or polyacrylonitrile.
4. The method for preparing the wheat-ear-shaped bismuth ferrite nanofiber absorbing material according to claim 1, characterized in that: In step (1), the mass ratio of bismuth nitrate pentahydrate, ethylene glycol methyl ether and spinning aid is 1: (0.97-4.86): (1.36-2.62).
5. The method for preparing the wheat-ear-shaped bismuth ferrite nanofiber absorbing material according to claim 1, characterized in that: In step (2), the electrospinning injection speed is 0.03-0.25 mm / min, the pinhole diameter is 20-25 G, the distance between the nozzle and the roller is 15-25 cm, the receiving speed of the roller is 30-60 r / min, the spinning positive voltage is 13-20 kV, the negative voltage is 0.5-3 kV, the temperature is 20-35 ° C, and the humidity is 20-40%.
6. The method for preparing the wheat-ear-shaped bismuth ferrite nanofiber absorbing material according to claim 1, characterized in that: In step (3), the drying temperature is 60-100°C, the time is 8-12h, and the vacuum degree is -0.08MPa.
7. The method for preparing the wheat-ear-shaped bismuth ferrite nanofiber absorbing material according to claim 1, characterized in that: In step (4), the calcination process is carried out in the following order: (a) In the first heating stage, the temperature is raised from room temperature to 260°C at a heating rate of 1-5°C / min and kept at this temperature for 1-3h; (b) the second heating stage, heating from 260°C to 340°C at a heating rate of 1-5°C / min, and keeping the temperature for 1-3h; (c) the third heating stage, heating from 340°C to 500°C at a heating rate of 1-5°C / min, and keeping the temperature for 1-3h; (d) Cooling stage: cooling to room temperature along with the furnace.
8. The method for preparing the wheat-ear-shaped bismuth ferrite nanofiber absorbing material according to any one of claims 1 to 7, characterized in that: The prepared wheat-ear-shaped bismuth ferrite nanofibers are applied in the field of wave-absorbing materials.
Citation Information
Patent Citations
Preparation method for bismuth ferrate nano fibers
CN102583566A
Bismuth ferrite nano fiber material and preparation method thereof
CN103451773A
Preparation method for porous hollow bismuth ferrite nano fibers
CN105386158A
Preparation method of bead curtain-like BiFeO3 micro-nanofiber and products obtained
CN106811832A
Preparation method and application of bismuth ferrite fibrous pyroelectric catalyst
CN113617359A